2014
DOI: 10.1115/1.4027688
|View full text |Cite
|
Sign up to set email alerts
|

Customizable Soft Pneumatic Chamber–Gripper Devices for Delicate Surgical Manipulation

Abstract: Traditional hard tissue grippers are limited in handling delicate soft tissues during surgery, particularly due to the high stress points that are generated on the soft tissue during gripping. In this study, customizable soft pneumatic chamber–gripper devices were designed to provide compliant gripping, so as to replace conventional tissue grippers such as the laparoscopic grasper or forceps in delicate tissue manipulation. The soft chamber–gripper device involves very simple design and control to generate act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Spiraling tentacles are widely utilized in nature for grabbing and squeezing objects. There have been continuous soft-robotic efforts to mimic them with pneumatic tube actuators 32 33 but the life-like, multi-turn spiraling motion has been reproduced only by centimeter-scale tentacles so far 5 34 At millimeter- and sub-millimeter scales, they could bend only up to a single-turn 12 14 31 35 Since the bending arises from the mismatch in the elongation levels of the tube’s top and bottom sides, it can be amplified into spiraling through mismatch enhancement. At macroscale, it is typically done with bi-elastomeric composite structures 5 or highly modulated surface corrugations 34 Neither is, however, easy to implement at microscale.…”
mentioning
confidence: 99%
“…Spiraling tentacles are widely utilized in nature for grabbing and squeezing objects. There have been continuous soft-robotic efforts to mimic them with pneumatic tube actuators 32 33 but the life-like, multi-turn spiraling motion has been reproduced only by centimeter-scale tentacles so far 5 34 At millimeter- and sub-millimeter scales, they could bend only up to a single-turn 12 14 31 35 Since the bending arises from the mismatch in the elongation levels of the tube’s top and bottom sides, it can be amplified into spiraling through mismatch enhancement. At macroscale, it is typically done with bi-elastomeric composite structures 5 or highly modulated surface corrugations 34 Neither is, however, easy to implement at microscale.…”
mentioning
confidence: 99%
“…Various application fields have been proposed for soft grippers made by FEAs. Low et al used two fingers to manipulate a surgical wire. Galloway et al showed the manipulation of delicate deep reefs (Figure ) and Zhou et al reported picking up of various food items, such as a banana, a pear, a piece of tofu, and an egg, using the integration of special materials in the palms of the grippers: a memory foam sheet and a patterned elastomeric layer.…”
Section: Gripping By Actuationmentioning
confidence: 99%
“…In addition to the main body of the surgical instruments, FEAs also represent a valid approach for developing soft yet effective tools. Grippers are among the most popular and with different implementations: a plate placed on the trajectory of a bending FEA; multiple bending actuators connected at their base; a traditional claw actuated by a linear fluidic soft actuator . Moreover, the bending of the device has been also used for supporting tasks, like retractors and forceps …”
Section: Surgical Toolsmentioning
confidence: 99%